Regulation, migration and the implications for industrial relations. (April 2019) - MacKenzie, Robert; Lucio, Miguel Martínez
The debate on migration has extended the scope of industrial relations research and brought questions of regulation to the centre. We suggest that there is a mutuality to the relationship between the debates around migration and regulation within the industrial relations literature: the study of migration has stimulated a new set of debates within industrial relations that allow us to reconsider issues of regulation; in turn, the study of regulation offers a useful perspective on issues relating to migration. The article applies an analytical framework based on the interplay of regulatory spaces and actors to the study of international migration. The framework offers a dynamic approach to mapping the wide range of actors involved in the regulation of migration and the boundaries between regulatory spaces, which may be fluid and contested. Through applying this framework, industrial relations issues relating to migration are located within a wider view of both regulation and the international movement of people.